Studies of aerosol physical properties in the coastal area - Zieliński, Tymon; Petelski, Tomasz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
In the marine boundary layer over coastal areas marine aerosol size distribution and concentration strongly depend on wind speed and location of the measuring point accross the surf zone. The measurements were taken from several stations on the Polish coast of the Baltic Sea by means of the lidar system FLS-12 and the laser particle counter CSASP-100-HV-SP. The results obtained provide valuable inputs for investigations of the physical processes, as well as an important data set for use in the development of aerosol type modeling and aerosol dynamics in the coastal areas.
Optica Applicata, Vol. 36, 2006, nr 4, s. 629-634
Keywords: optyka; aerosol; physical properties; marine boundary layer; surf zone